848 SURAU SULUK, MURSYID DAN PENGOBATAN TRADISIONAL DI KABUPATEN LIMA PULUH KOTA - NFN Hariadi (Balai Pelestarian Nilai Budaya Sumatera Barat, 2018)
Medicinal treatment or therapy by Mursyid is another side of Surau suluk (Suluk mosque) that isstudied rarely. This study aims to explain the traditional therapy done by Mursyid in suluk mosques inLima Puluh Kota regency, West Sumatera. This research used descriptive qualitative approach. Thedata were collected by doing literature review, field observation, and in-depth interview. The informantswere several Mursyid from some suluk mosques and also the people who get involved in suluk activitiesand therapy. The result of data analysis explained that traditional therapy done by Mursyid in sulukmosques are based on zikrulloh. The therapy is done on medical and non medical diseases, however, itis focused more on non medical diseases such as possession of the jin (evil spirit).